Quran, name, and scientific communication - Ajat Sudrajat; Ita Rahmania Kusumawati (Informasi, 2021)
The objective of this study is to investigate the views of the Qur'an about the origin of the name and its position in relation to language and the development of science. The research model is literature research utilizing the sources collection (heuristic), source criticism, interpretation, and writing. The findings of this study are: (1) the Qur'an states that Allah SWT gives teachings about the names to the Prophet of Adam As; (2) These names correlate with the language because they are composed of the names that have been introduced to the Prophet Adam As; (3) The name and language are two sides of money; (4) Names, languages, and concepts can further be the main capital that humans have to develop scientific communication.